CFD-Based Performance Optimization of Overlap Ratio in Savonius Hydrokinetic Turbines for Riverine Energy Systems - Muhyiddin, Mohammed; Shamsul, Sarip; Sa'ardin, Abdul Aziz (The Italian Association of Chemical Engineering, 2025)
This paper offers a numerical investigation of the performance of Savonius hydrokinetic turbines with three distinct blade overlap ratios: positive (+1.5), neutral (0), and negative (–1.5). The study employed twodimensional transient simulations in ANSYS Fluent, using the Shear Stress Transport (SST) k-ω turbulence model, to assess turbine performance in low-speed riverine currents with an input velocity of 0.8 m/s. The overlap configurations were assessed across a range of tip speed ratios (TSR), with results compared in terms of power coefficient (Cp), torque response, and flow characteristics. The 0-overlap configuration achieved the highest efficiency, recording a peak Cp of 0.0794 at TSR 1.3. The 0-overlap configuration achieved the highest efficiency, recording a peak Cp of 0.0794 at TSR 1.3. This performance can be attributed to the balanced interaction between the advancing and returning blades, which minimizes flow interference. Compared to typical small-scale horizontal-axis turbines operating under similar flow conditions, the observed Cp remains modest but favorable for low-speed riverine applications. The standard deviation associated with this peak Cp value was approximately ±0.0021, based on time-averaged torque data over multiple cycles. The +1.5 design performed best at TSR 1.8 with Cp 0.0631, while the –1.5 case reached its peak Cp of 0.048 at TSR 0.7, offering smoother start-up performance at low rotational speeds. Pressure and velocity contours revealed distinct flow behaviors across geometries: smooth flow and minimal wake in the 0-overlap case, moderate separation for +1.5, and strong vortex shedding with wide wake for −1.5, each correlating with their respective performance trends. These findings underscore the impact of blade overlap on energy extraction and offer valuable guidance for the design of riverine small-scale hydro turbines.